Developing Descriptive Writing Graphic Organizers’ of the Students at the Eighth Grade of SMP Swasta Kristen Agios Nikolaus in 2022/2023 - Zega, Yudika; Harefa, Afore Tahir; Zebua, Elwin Piarawan; Telaumbanua, Yasminar Amaerita (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
Based on the preliminary data, it was found that students in SMP Swasta Kristen Agios Nikolaus were still unable to write descriptive texts. This is because the media used by the teacher is only in the form of a table on a piece of paper and is less interesting. This research aims to develop a learning media in writing descriptive text in the form of Graphic Organizers (GOs). The method used in this research is Research and Development (R & D) using the ADDIE model. There are several procedures in the ADDIE model, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Based on the results of the study, it was found that the graphic organizers media were declared